Agriculture and ASEAN Economies: Still Key for Growth - Teng, Paul (2016)
Despite its declining contribution to the GDP of ASEAN economies, agriculture remains a major source of employment for rural populations and provides much value add for agrifood industries. The ASEAN region needs to tap more public- private synergies so that agriculture’s contribution to economic growth is fully utilized.